The Mediating Role of E-Satisfaction in the Relationship between E-Service Quality and Customer E-Loyalty in Internet Banking - Al-Dmour, Rand; Alnafouri, Muhammed; Al-Alwan, Ali (Jordan Journal of Business Administration, 2019)
This study aims at examining the impact of e-service quality on e-loyalty and the mediating role of e-satisfaction in this relationship among Jordanian customers of internet banking. A pre-designed questionnaire was distributed to 500 full-time adults working in Amman by e-mail as well as by hand. The response rate was 79.40%. The empirical findings of the study confirmed that there was a positive significant relationship between e-service quality and e-loyalty and proved the role of e-satisfaction as a mediator in internet banking industry. These findings may aid future researchers in understanding the inherent relationships that lie between the constructs’ questions and may provide a platform for banking managers in their efforts to improve internet customer banking service.